2020
DOI: 10.17707/agricultforest.66.2.07
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Effect to Productivity of Bioenergy Crop Miscanthus X Giganteus in Different Environments

Abstract: Miscanthus x giganteus Greef et Deu is a perennial C4 grass, originally from East Asia. Morphological productive characteristics of miscanthus were analyzed in this study: plant height in the tasseling period, number of leaves on stalk in the tasseling period, number of stalk in tiller, number of stalk with tassel, dry plant yields, stalk moisture in harvest time and cellulose content. The miscanthus achieves high yields and excellent performance in summer drought conditions because it has a well-developed roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…Studies of quality of miscanthus stalks grown in different agroecological conditions in Serbia, Refs. [6,7], concluded that growing conditions and applied agrotechnical measures did not have any major impact on the chemical composition of aboveground biomass, since during the maturation of plants, i.e., stalks, the highest percentage of nutrients is transferred to rhizomes. Two-factor analysis of variance of the examined traits is presented in Table 7.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of quality of miscanthus stalks grown in different agroecological conditions in Serbia, Refs. [6,7], concluded that growing conditions and applied agrotechnical measures did not have any major impact on the chemical composition of aboveground biomass, since during the maturation of plants, i.e., stalks, the highest percentage of nutrients is transferred to rhizomes. Two-factor analysis of variance of the examined traits is presented in Table 7.…”
Section: Resultsmentioning
confidence: 99%
“…It is characterized by extremely strong growth and high genetic potential for fertility [6], and is becoming important as an energy crop. As a consequence of its triploidy, miscanthus does not produce fertile seeds, so there is no possibility of the plants spreading outside their plantations and forming weeds in surrounding agricultural areas [7]. Miscanthus is mainly grown for the production of biofuels from aboveground biomass.…”
Section: Introductionmentioning
confidence: 99%
“…2012). Производња разних ратарских и енергетских биљака у великој мјери зависи од примијењене технологије производње(Popović et al 2019а,б;Mladenović-Glamočlija et al 2020), али изузетно много и од метеоролошких услова, првенствено од температуре и падавина током вегетационог периода(Popović et al 2011(Popović et al , 2012а,б, 2013(Popović et al ,а,б, 2015(Popović et al , 2016Sikora et al 2016Sikora et al , 2019 Tab. 8.1.…”
unclassified